3D Model Bahan Ajar Pengenalan Hewan Berbasis Augmented Reality - Apridiansyah, Yovi; Wibowo, Sastya Hendri; Muntahanah, Muntahanah; Apriansyah, Nugraha (Jurnal Media Infotama, 2025)
his study aims to develop an interactive learning media based on Augmented Reality (AR) technology to support the introduction of animals to elementary school students. The learning media is designed in the form of 3D animal models that visually represent the name, habitat, and characteristics of each animal. The 3D models were developed using Blender software and implemented into the AR Web Studio platform, allowing users to scan markers using a mobile device camera and display animal objects in real-time. The research method used is Research and Development (R&D), consisting of several stages: problem formulation, data collection, media development, implementation, and system evaluation. Testing was conducted using two approaches: technical testing with the black-box method and user testing through questionnaires distributed to several elementary school teachers. The technical testing results showed that all system features, such as marker detection, 3D model display, and user interaction, functioned properly. Meanwhile, user testing revealed an average satisfaction score of 76.9%, which falls into the “Good” category. Based on these results, it can be concluded that the AR-based animal learning media is feasible to use and provides a positive contribution to increasing students’ interest and understanding of the learning material in an interactive manner.